ROOTING OF GUANANDI (Calophyllum brasiliense CAMBESS) CUTTINGS USING INDOLE-BUTYRIC ACID - Ciriello, Eduardo; Mori, Edson Seizo [UNESP] (Univ Federal Lavras-ufla, 2015)
Commercial reforestation of Brazilian native species to produce hardwood for sawmills has been recently intensified in the country. Among the potential species planted by the logging industry is guanandi (Calophyllum brasiliense Cambess) because it is widely distributed in the country, highly adapted to different soil and climate conditions, good bole form and high quality timber. The development of genetic improvement programs should prioritize gains in productivity and yields in the medium and long term. For such programs to be successful, the study of vegetative propagation techniques to abbreviate steps in forest improvement and allow its mass production is fundamental. To assess the viability of vegetative propagation of the species, two successive experiments were carried out during two years testing the best type of cutting, hormone concentration and management. Different cuttings types submitted to increasing doses of indole-butyric acid (IBA) were tested to evaluate survival, sprouting, rooting and callus formation. Results indicate that the species is viable for vegetative propagation with 85 to 90% rooting of cuttings from seedlings in the IBA concentrations of 3000 to 7000 mg.L-1. For the cuttings, sprouting from the base of adult trees 3000 mg.L-1 was the best concentration of IBA.
Keywords: Improvement programs; Adventitious roots; Vegetative propagation